2012
DOI: 10.1103/physrevlett.109.097403
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation Dynamics of Photoexcited Excitons in Rubrene Single Crystals Using Femtosecond Absorption Spectroscopy

Abstract: The relaxation dynamics of an exciton in rubrene was investigated by femtosecond absorption spectroscopy. Exciton relaxation to a self-trapped state occurs via the coherent oscillation with 78 cm(-1) due to a coupled mode of molecular deformations with phenyl-side-group motions and molecular displacements. From the temperature dependence of the decay time of excitons, the energy necessary for an exciton to escape from a self-trapped state is evaluated to be ~35 meV (~400 K). As a result, a self-trapped exciton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 27 publications
2
37
0
Order By: Relevance
“…We do not rule out the contribution of exciton states with different symmetry (N or L, transition from higher excited states) in amorphous rubrene, because the difference between the first and the second peak is 0.16 eV rather than the carbon double bond vibration of 0.18 eV. This picture is complicated by Tao et al, 18 who showed the existence of a self-trapped state with a depth of 35 meV in rubrene crystals arising from coupled modes of molecular deformations with phenyl side groups. It is possible that these self-trapped excitons exist in amorphous rubrene as well.…”
Section: A Steady State Photophysicsmentioning
confidence: 90%
“…We do not rule out the contribution of exciton states with different symmetry (N or L, transition from higher excited states) in amorphous rubrene, because the difference between the first and the second peak is 0.16 eV rather than the carbon double bond vibration of 0.18 eV. This picture is complicated by Tao et al, 18 who showed the existence of a self-trapped state with a depth of 35 meV in rubrene crystals arising from coupled modes of molecular deformations with phenyl side groups. It is possible that these self-trapped excitons exist in amorphous rubrene as well.…”
Section: A Steady State Photophysicsmentioning
confidence: 90%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] However, our theoretical understanding of these processes is still lacking in many cases. At the most basic level, one may describe the energy transport as a quantum diffusion process occurring in a system that is influenced by both static disorder and thermal fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…Tao et al 25 studied the relaxation dynamics of photoexcited excitons in rubrene crystal by use of temperaturedependent transient absorption spectroscopy. They show that within 100 fs free excitons relax to self-trapped excitons via coherent oscillation.…”
mentioning
confidence: 99%